Prophetic Communication in Character Building: A Case Study of Muhammadiyah Boarding School (MBS) Jetis Ponorogo - Rahmawati, Alfiana Yuniar (Jurnal Dakwah, 2023)
This study explores the implementation of prophetic communication in the character building of students at Muhammadiyah Boarding School (MBS) Jetis Ponorogo. Prophetic communication, rooted in the teachings and practices of the Prophet Muhammad, serves as a fundamental approach in shaping the moral and spiritual character of students in Islamic education. The study utilizes a qualitative method, incorporating observations, interviews, and document analysis to examine how MBS Jetis Ponorogo integrates prophetic communication into its educational practices. The findings reveal that the use of prophetic communication significantly contributes to the development of students' character, fostering qualities such as integrity, compassion, and discipline. This study underscores the importance of embedding prophetic values in educational settings to cultivate well-rounded individuals who embody both religious and ethical principles in their daily lives.